2009
DOI: 10.1128/aac.00657-09
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans and Staphylococcus aureus Form Polymicrobial Biofilms: Effects on Antimicrobial Resistance

Abstract: Candida albicans readily forms biofilms on the surface on indwelling medical devices, and these biofilms serve as a source of local and systemic infections. It is estimated that 27% of nosocomial C. albicans bloodstream infections are polymicrobial, with Staphylococcus aureus as the third most common organism isolated in conjunction with C. albicans. We tested whether S. aureus and C. albicans are able to form a polymicrobial biofilm. Although S. aureus formed poor monoculture biofilms in serum, it formed a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
414
4
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(442 citation statements)
references
References 29 publications
18
414
4
6
Order By: Relevance
“…1). This association has been reported by Harriott & Noverr (2009), where St. aureus was shown to be embedded in the fungal biofilm matrix. Significantly, this close association between C. albicans and St. aureus in a biofilm conferred resistance to antibiotics upon St. aureus.…”
Section: Discussionmentioning
confidence: 62%
“…1). This association has been reported by Harriott & Noverr (2009), where St. aureus was shown to be embedded in the fungal biofilm matrix. Significantly, this close association between C. albicans and St. aureus in a biofilm conferred resistance to antibiotics upon St. aureus.…”
Section: Discussionmentioning
confidence: 62%
“…Synergised recalcitrance to antimicrobials has also been observed in several studies [80, 81, 82••]. Pioneer studies from Harriot and Noverr (2009) identified a biofilm-mediated resistance against vancomycin within the dual-species biofilm [81]. More recently, the precise mechanism of this resistance has been elucidated, with a suggestive "barrier mechanism," whereby S. aureus coats itself in secreted C. albicans matrix molecules to impede drug penetration within the biofilm [82••].…”
Section: Angular Cheilitis: Partners In Crime or Peer Pressure?mentioning
confidence: 87%
“…Candidiasis, caused by Candida species, is the most common fungal infection in humans and animals. Candida albicans is considered the most prevalent fungal biofilmforming pathogen that causes life-threatening infections by colonizing polymers used in medical devices [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%